2020
DOI: 10.1042/bsr20200471
|View full text |Cite
|
Sign up to set email alerts
|

Cimifugin ameliorates imiquimod-induced psoriasis by inhibiting oxidative stress and inflammation via NF-κB/MAPK pathway

Abstract: Cimifugin is an important component of chromones in the dry roots of Saposhikovia divaricata for treating inflammatory diseases. However, the possible effect of cimifugin in psoriasis needs further investigation. This current work was designed to evaluate the effects of cimifugin in psoriasis in vivo and in vitro, and unravel the underlying molecular mechanism. Here, we used imiquimod (IMQ) or tumor necrosis factor (TNF)-α to induce a psoriasis-like model in mice or keratinocytes. Obviously, the results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…Previous studies prove that CIM has potential to multiple in ammatory diseases. Liu et al 14 Moreover, all these three studies including the present one only investigate the level of signaling proteins in limited number, so it seems impossible to come to an agreement for now.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous studies prove that CIM has potential to multiple in ammatory diseases. Liu et al 14 Moreover, all these three studies including the present one only investigate the level of signaling proteins in limited number, so it seems impossible to come to an agreement for now.…”
Section: Discussionmentioning
confidence: 82%
“…Given this, we investigated a natural compound called Cimifugin (CIM) as one of main components of Saposhnikovia Divaricata or Cimicifuga Racemosa extract 10; 11 . CIM is commonly reported as a bioactive chromone independently or in multiple Chinese medicine formulae with reported properties of antinociception, antiin ammation and lipid metabolism regulation in a spectrum of diseases, including allergy in skin and respiratory system, in ammatory arthropathies, and cerebral ischemia by inhibiting the production of in ammatory factors and NF-kb/MAPK signaling [11][12][13][14][15][16] . However, in term of the treatment for ALP, the bioactivity of CIM has not been investigated in osteoclastogenesis and subsequent periprosthetic osteolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase of IL-1β can stimulate synovial fibroblasts, chondrocytes and osteoclasts to produce tissue-damaging matrix metalloprotease (MMP), leading to bone loss (Sirikaew et al, 2019). Numerous published reports have shown that osthole, cimifugin, 5-O-methylvisammioside, albiflorin, paeoniflorin and icariin, the active components of WBC, can directly or indirectly regulate nuclear factor kappa-B or other signal pathways and reduce the contents of inflammatory cytokines IL-1β and PGE 2 (Liu et al, 2020;Xu et al, 2018). Therefore, PGE 2 and IL-1β were selected as PD indicators in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of the phosphorylated forms of ERK1/2 and p38, not JNK, were also significantly higher in the lesional psoriatic skin [ 45 ]. The suppression of MAPK signaling pathways by a natural compound, cimifugin, significantly attenuated inflammation in both in vitro and in vivo models of psoriasis [ 46 ]. In the present study, PSM blocked the phosphorylation of ERK1/2, p38, and STAT3 significantly in M5-stimulated HaCaT cells, suggesting that the therapeutic action of PSM might be through inhibition of the ERK1/2, p38, and STAT3 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%